PENGEMBANGAN DESA WISATA TANAMAN OBAT DALAM RANGKA PEMBERDAYAAN MASYARAKAT PEDESAAN - Hariadi Darmawan; Zuhdi Ma’sum; Akhirul Aminulloh (Universitas Tribhuwana Tunggadewi, 2017)
Abstract: The purpose of this is to support the activities IBW Local Government Pacitan District in terms of democratic economic development prioritizing agro-industrial sector of medicinal plants. Therefore, IBW team Tribhuwana Tunggadewi University and National Institute of Technology in Malang proposed program IBW Tourism Village in the district of Medicinal Plants Nawangan, Pacitan. The final target of the program is the tourist village of medicinal plants by the development of integrated and sustainable agricultural systems are based on self-reliance and environmentally sound. Implementation of the program's first year IBW tourist village in the district of medicinal plants Nawangan Pacitan district is focused on the activities of